Synergistic effect in the catalytic activity of lipase Rhizomucor miehei immobilized on zeolites for the production of biodiesel - de Vasconcellos, Adriano [UNESP]; Paula, Alex S. [UNESP]; Luizon Filho, Roberto A. [UNESP]; Farias, Lucas A.; Gomes, Eleni [UNESP]; Aranda, Donato A. G.; Nery, Jose G. [UNESP] (Elsevier B.V., 2012)
Gismondine (P) ion exchanged with Cu2+, Zn2+, and Ni2+ were used as solid supports for the immobilization of the lipase Rhizomucor miehei enzyme. Physicochemical characterization of the zeolite-enzyme complexes were performed by X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM) and attenuated total reflectance-Fourier transform infrared (ATR-FTIR). These bio-catalysts were used for the transesterification reaction of soybean oil to biodiesel. Divalent cation species and thermal treatment of the zeolitic supports had different effects on several parameters under investigation. In terms of the enzyme activity, the zeolite-enzyme complexes prepared with Ni-P were superior in comparison to the other ones and a synergistic effect for the zeolite-enzyme complex (Ni-P/200-ENZ) was observed for the transesterification reactions of soybean oil to biodiesel. The total amount of methyl esters produced by the complex Ni-P/200-ENZ was of 56.2%, while the same concentration of the immobilized enzyme in its free form yielded only 39.3% of methyl esters, and Ni-P/200 in its pure form also yielded a very low amount of methyl esters (20%). The other zeolite-enzyme complexes (Zn-P/200-ENZ, Cu-P/200-ENZ, and Na-P/200-ENZ) presented a completely different behavior in comparison to the Ni-P/200-ENZ complexes. The total yields of methyl esters generated by these biocatalysts were very low and no synergistic effects were observed. A correlation between the cation atomic radius and the enzymatic activity of the zeolite-enzyme complexes was observed. It was noticed that the bigger the atomic radius of the extra-framework cation, smaller was the experimental enzymatic activity coefficient. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Lipase enzyme; Zeolite P; Enzyme immobilization; Transesterification reactions; Biodiesel